Forced swim test behavior in postpartum rats - Craft, R.M. (2010)
This study was undertaken to determine whether depression-like behavior can be observed in gonadally intact females that have experienced normal pregnancy. When tested on the forced swim test (FST) on postpartum days 1-7, previously pregnant rats spent slightly more time immobile, significantly less time swimming and diving, and defecated more than virgin controls. Subchronic treatment with nomifensine (DA reuptake inhibitor, 2.5 mg/kg) but not sertraline (serotonin reuptake inhibitor, 10 mg/kg) or desipramine (norepinephrine reuptake inhibitor, 10 mg/kg) significantly decreased immobility on postpartum day 2. In rats pre-exposed to the FST in mid-pregnancy, neither subchronic nor chronic treatment with desipramine or sertraline decreased immobility on postpartum day 2; in contrast, chronic desipramine significantly decreased immobility in virgin controls. These results indicate that postpartum female rats, compared to virgin controls, show a reduction in some “active coping behaviors” but no significant increase in immobility when tested during the early postpartum period, unlike ovariectomized females that have undergone hormone-simulated pregnancy (HSP). Additionally, immobility that is increased by FST pre-exposure is not readily prevented by treatment with standard antidepressant medications in postpartum females. Depression-like behaviors previously observed in females that have undergone HSP may result from the more dramatic changes in estradiol, prolactin or corticosterone that occur during the early “postpartum” period, compared to the more subtle changes in these hormones that occur in actual postpartum females.